Characteristics of Fournier gangrene and evaluation of the effects of negative-pressure wound therapy - He, Rui; Li, Xiangyan; Xie, Kun; Wen, Bing; Qi, Xin (Frontiers in Surgery, 2023)
Fournier gangrene (FG) is a life-threatening disease affecting the soft tissues of the genital, perineal, and perianal regions. This retrospective study aimed to summarize the characteristics of FG and evaluate the effects of negative-pressure wound therapy (NPWT). We analyzed clinical data of 36 patients with FG admitted to our department. Thirty-four cases had perianal and external genital infections, and the other two had secondary infection of the urinary fistula after trauma and retroperitoneal abscess, respectively. Monomicrobial, polymicrobial, culture-negative, and fungal infections were identified in 16, 17, 2, and 1 cases, respectively. Escherichia coli, Enterococcus faecalis, Enterococcus faecium, Klebsiella pneumoniae, and Staphylococcus haemolyticus were the most common pathogens. The mortality rate was 8%. Twenty-seven and nine patients were treated with NPWT (group A) and conventional dressing (group B), respectively. The length of stay was 38.0 ± 16.1 and 51.0 ± 17.3 days, number of operations were 3 (3,6) and 13 (4,17), and wound healing times were 39.2 ± 18.1 and 66.5 ± 17.1 days in groups A and B, respectively. Taken together, clinicians should always consider the possibility of perianal or external genital infections progressing to FG in the daily work, especially for patients with diabetes mellitus. Enterobacteriaceae, Enterococcus, and Staphylococcus haemolyticus are the most common causative pathogens, and NPWT is an effective adjuvant therapy for wound management with fewer operations and a shorter wound healing time.